-8c=-9c+3

Simple and best practice solution for -8c=-9c+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8c=-9c+3 equation:



-8c=-9c+3
We move all terms to the left:
-8c-(-9c+3)=0
We get rid of parentheses
-8c+9c-3=0
We add all the numbers together, and all the variables
c-3=0
We move all terms containing c to the left, all other terms to the right
c=3

See similar equations:

| 8|x+7|+4=-6|x+7|+6 | | w–53=1 | | 5-3v=-4v | | -y–112=7 | | 88=16+6(t+8) | | -w4–1=-1 | | 3d+8=d-6 | | 3(4+c)=-15 | | 48=4(w+11) | | 55=15+10(11+x) | | 444+181=h | | 20=5a-a | | 2/3x+5/12=1/6x-5/6 | | -10r=-8r+6 | | 18w-9w=9 | | x+70=11x-70 | | -3+3k=k+9 | | 2x+9=3x-1+8 | | -3=q-7/3 | | 2(w+9)=-6 | | 20=4(t+1 | | 5c=-6+8c | | -5-6h=-7h | | (x+1)=(3x+4) | | 7+r=14 | | 17=c/3-13 | | 17=c/3-1 | | 2(h-20)=-12 | | 7-z=-14 | | -10+x=6.5 | | 6.5=-10+x | | -12d+24=-12 |

Equations solver categories